Proučevanje biomehanike kolena v prostoru - Veselko, Matjaž (Medicinski razgledi, 1999)
Studying the biomechanics of the knee is a demanding task because of the complexity of the knee joint motion. Many methods have been described in the literature, yet most of them do not consider movements in three axes and threeplanes. Lately, some precise mechanical and optical methods have been developed for the study of three-dimeneional biomechanics of the knee. The paper presents our original method for studying the threee-dymensional biomechanics of the knee based on the determination of the rigid body geometryin the body-fixed reference frame and the orientation of the body-foced reference frame in the global co-ordinate system. The data in the form of the Cartesian frame co-ordinates are gathered by the co-ordinate measuring machine. The method is compared to other similar methods. The advantage of our method is that it allows an accurate study of biomechanics ofotherwise inaccessible structures of the joint.
Keywords: Knee joint; koleno; kolenski sklep; Biomechanics; biomehanika; Cadaver; metode; Movement; Range of motion, articular